An in vivo critically colonised wound model with dysbiotic wound microbiota. Issue 3 (6th August 2022) - Kunimitsu, Mao; Nakagami, Gojiro; Minematsu, Takeo; Koudounas, Sofoklis; Sanada, Hiromi
Abstract: In critically colonised wounds, many of the signs of infection are often absent, and delayed healing may be the only clinical sign. The prevention of critical colonisation is important, but its pathophysiology has not yet been elucidated. We have previously reported that dysbiotic microbiota dissimilar to the peri‐wound skin microbiota may develop in critically colonised wounds. To investigate the role of dysbiotic microbiota, this study aimed to develop a critically colonised wound model by transplantation of dysbiotic microbiota. To transplant microbiota, a bacterial solution (dysbiosis group) or with Luria‐Bertani medium (commensal group) was inoculated to full‐thickness wounds of rats. The bacterial solution was prepared by anaerobically culturing bacteria from donor rats on an artificial dermis in Luria‐Bertani medium for 72 hours. As a result, the degree of the change in the microbial similarity between pre‐ and post‐transplantation of microbiota was significantly higher in the dysbiosis group ( P < .001). No signs of infection were observed in any rat in either group. The wound area in the dysbiosis group was significantly larger ( P < .001), and there was a significant infiltration of neutrophils ( P < .001). All rats of the dysbiosis group represented the clinical features of critically colonised wounds. Furthermore, there were significantly fewer regulatory T cells in the wounds of the dysbiosis group. This is the first study to develop a novel animal model that represents the clinical features of critically colonised wounds and will be useful in investigating the pathogenesis of critical colonisation via regulatory T cells.